KEPEMIMPINAN TRANSFORMASIONAL CAMAT DI KANTOR KECAMATAN SUNGAI TABUKAN KABUPATEN HULU SUNGAI UTARA - M. Ridha Anshari (Cross-border, 2021)
This research started from the writer's curiosity about the transformational leadership of the sub-district head at the Sungai Tabukan District Office, Hulu Sungai Utara Regency. The approach used is quantitative research methods collected through the distribution of previously prepared questionnaires. This type of research is explanatory research and aims to provide an explanation of why something happens or answer the question "why". The results of this study indicate that 1) the factor of openness to experience (X1) on transformational leadership (Y) the Camat at the Sungai Tabukan District Office has a positive and significant influence. 2) Conscientiousness factor (X2) on transformational leadership (Y) The sub-district head at Sungai Tabukan sub-district office has a positive and significant influence. 3) The Agreeablenes factor (X3) on transformational leadership (Y) the Camat at the Sungai Tabukan Subdistrict Office has a positive and significant influence. 4) The factor of emotional intelligence (X4) on transformational leadership (Y) The Camat at the Sungai Tabukan District Office has a positive and significant influence. 5) The motivational factor (X5) on transformational leadership (Y) the Camat at the Sungai Tabukan District Office has a positive and significant influence. 6) The decision-making factor (X6) on transformational leadership (Y) the Camat at the Sungai Tabukan District Office has a positive and significant influence. 7) The factors of openness to experience, conscientiousness, agreeableness, emotional intelligence, motivation, and decision making together have a significant effect on transformational leadership, this can be proven by the F-test results obtained that the F-count is 23,286 greater than the F table 2,016 at the level of sig. 0.00.